Analysis of Online Community Services in Problem Solving Studying at Open University: A Case Study to Improving Problem-Solving Ability of PGSD - Dwikoranto; Titik Setyowati; Suparti; Sulistyono; Widiasih (Indonesia Approach Education, 2022)
The purpose of this study is to analyze problems in online communities to help solve problems faced by Open University (OU) students in terms of topics discussed in online communities, problems that arise in online communities, the process of counseling guidance in online communities, improving student problem-solving skills after discussing in online communities. This research was conducted using a quantitative descriptive design. All Elementary School Teacher Education (PGSD) students who post on online community services, from January 2019 to December 2019 as research objects. Data were collected using the documentary method and a problem-solving ability test for students from the Bojonegoro study group. Data from the online community is described based on the proportions while the problem-solving ability with N-gain, sensitivity, and completeness. The results showed: (1) The topics discussed in the online community service were introductions, registration, tutoring/study, and grades/exams; (2) Problems that arise in online community services are registration, tutorials, grades, and exams; (3) The process of counseling guidance in online community services for student problems is karstic; (4) Students' problem-solving ability after discussing in online community services increases and is in high criteria.